The expressive use of masks across cultures and healing arts - Ridley, Susan (Routledge, 2024)
"The Expressive Use of Masks Across Cultures and Healing Arts explores the interplay between masks and culture and their therapeutic use in the healing arts such as music, art, dance/movement, drama, play, bibliotherapy, and intermodal. Each section of the book focuses on a different context including viewing masks through a cultural lens, masks at play, their role in identity formation (persona and alter ego), healing the wounds from negative life experiences, from protection of medical masks to helping the healing process, and expressions of grief to celebrating life stories. Additionally, the importance of cultural sensitivity, including the differences between cultural appreciation and appropriation is explored. Chapters are written by credentialed therapists to provide unique perspectives on the personal and professional use of masks in the treatment of diverse populations in a variety of settings. A range of experiences are explored from undergraduate and graduate students to early professionals and seasoned therapists. The reader will be able to adapt and incorporate techniques and directives presented in these chapters. Readers are encouraged to explore their own cultural heritage, to find their authentic voice, as well as learn how to work with clients who have different life experiences"--